International Non-muslim Tourist Satisfaction With Islamic And Generic Destination Attributes In Jeddah, Saudi Arabia - Basendwah, Mohammed Abdulrahman A (2024)
Saudi Arabia has traditionally been a hub for religious tourism. With the introduction of the 2030 Vision, the country expands its tourism offering beyond religious tourism. This shift marks a strategic realignment to attract more diverse global travellers by implementing regulations designed to enhance the destination's appeal. Despite these ambitious reforms, there remains a critical gap in understanding the experience of tourists from diverse cultural and religious backgrounds when navigating conservative Islamic customs in a Muslim-majority country. Moreover, given that Saudi Arabia's tourism sector primarily focused on religious pilgrimages before the introduction of the leisure tourist visa in 2019, further research is needed on the satisfaction of international tourists visiting for non-religious activities. Literature shows that studies utilising the disconfirmation theory are scarce within the context of Islamic destination attributes. By utilising the disconfirmation theory, this study examines international non-Muslim tourists' satisfaction with Islamic destination attributes as well as the generic ones within the context of Jeddah city. Tourist satisfaction was assessed using the HOLSAT model, while the influence of Islamic and generic attributes on travel satisfaction was evaluated utilising the Expectancy Disconfirmation Model (EDM), with the aim to determine whether Islamic attributes hinder the success of the travel experience of non-Muslim tourists. Notably, the study's conceptual model, which is grounded in the EDM, was slightly modified to incorporate the loyalty variable.